Peningkatkan Hasil Belajar Pai Melalui Metode Pembelajaran Diskusi Pada Kelas VII di UPTD SMPN 1 Kec. Harau - M. Rezki Suhatris Hisham; Zulfani Sesmiarni; Rodi Rodi; Nasrul Nasrul; Ikrar Dinata; Jekis Wardi (LPPI Yayasan Almahmudi bin Dahlan, 2024)
The success of learning objectives is determined by many factors including the teacher's factor in carrying out the teaching and learning process, because the teacher can directly influence, foster and improve students' intelligence and skills. To overcome the above problems and to achieve maximum educational goals, the role of the teacher is very important and it is hoped that the teacher has a good teaching method and is able to choose the right learning method and in accordance with the concepts of the subject to be conveyed. The problems to be studied in this study are: The purpose of this action research is to improve PAI learning outcomes through the use of discussion learning methods in class VII UPTD SMPN 1 Kec. Harau.This study used one round of class action research. Each round consists of four stages, namely: planning, implementation, observation, reflection. The target of this research is class VII students of UPTD SMPN 1 Kec. Harau. The data obtained are quantitative and qualitative data. From the results of the analysis, it can be seen that the students' understanding of the material presented by the teacher is getting stronger (learning completeness increased from cycle I, to III, namely 61.76%, and 82.00% respectively. In cycle III, classical student learning completeness was achieved. The conclusion of this research is that the discussion learning method has a positive influence, which can improve student learning outcomes as indicated by the average student answers which state that students are interested and interested in the discussion learning method so that they become motivated to learn.